Behind the gates of learning: Exploring the educational experiences of teachers and children in conflict with the law in Malaysian rehabilitation centres - Md Taib, Rosfizah; Wan Mustaffa , Wan Salmun (Journal of Islamic, Social, Economics and Development, 2025)
Education plays a pivotal role in the rehabilitation and reintegration of Children in Conflict with the Law (CCL). In Malaysia, institutional rehabilitation centres are mandated to provide educational and vocational programmes aimed at restoring disrupted learning trajectories and fostering personal transformation. This qualitative thematic article examines the challenges, expectations, and reintegration pathways associated with educational provision for CCL, drawing on insights from teachers and former child offenders. Findings reveal systemic constraints related to resources, family support, stigma, employability, and self-resilience, while simultaneously highlighting education as a source of hope, moral reform, and future orientation. The article contributes to policy and practice by underscoring the need for coordinated post-release support, family engagement, and societal acceptance to sustain rehabilitation outcomes.